Dispersed Capacity and Weak Coordination: The Challenge of Climate Change Adaptation in Canada's Forest Policy Sector. Issue 1 (9th January 2013) - Rayner, Jeremy; McNutt, Kathleen; Wellstead, Adam
Abstract Constitutional and institutional legacies were combined to create a very decentralized forest policy sector in Canada. Where coherent policy requires a national response—as is the case with adaptation to climate change—the critical challenge is to locate the relevant decentralized policy capacity and steer it toward meeting national objectives. While there is some evidence that significant policy capacity exists in provincial forest and resource management departments, climate change adaptation has led to an expansion of departmental mandates that is not being addressed by better coordination of the available policy capacity. The relevant federal agencies are not well represented in information networks and forest policy workers report lower levels of internal and external networking than workers in related policy subsectors.